Smart Touch Voltage Limitation - Mahmut Turhan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In modern railway electric infrastructure design there are two major concerns that should be considered as touch voltage and stray current. The first problem is touch and step voltage which endangers human safety even to deathly situations. Second problem is stray current which leads to corrosion of metallic infrastructure. Since human safety has higher priority early on railway systems has grounded the rail voltage to the earth but this caused stray current problem. Thus these two problems should be handled together. In this paper we present a touch voltage control and stray current monitoring solution to handle both problems. Our solution presented here uses thyristor based grounding to limit touch voltage and monitor and report stray current